Development of Macular Edema and Impact on Visual Acuity in Uveitis Associated with Juvenile Idiopathic Arthritis*. (February 2015) - de Boer, Joke; Steijaert, Arjen; van den Bor, Rutger; Stellato, Rebecca; Ossewaarde-van Norel, Jeannette
Abstract Purpose: To investigate the development of macular edema (ME) in relation to the duration of uveitis and visual outcome in uveitis associated with juvenile idiopathic arthritis (JIA). Methods: Sixty-one patients with JIA-uveitis (116 eyes) were investigated by Cirrus OCT for macular thickness. The relation between macular thickness and time interval since onset of uveitis and best corrected visual acuity (BCVA) was analyzed by linear mixed effect models. Results: Duration of follow-up showed significant positive linear relation with central macular thickness. The central macular thickness showed a significant linear relation with BCVA, but not with disease activity. Thirteen patients developed ME (central field thickness >304.4 µm) after a mean time interval of 11.6 years. Thirteen patients had macular thinning after a significant longer interval of uveitis compared to patients with normal or thickened macula. Conclusions: Duration of JIA-uveitis is positively correlated with the development of ME, compromising the visual acuity.